The Potential of Halal Micro, Small, and Medium Enterprises and Halal Lifestyle in Building the Indonesian Economy - Rigina Melati, Risni; Amirudin, Choirul (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: Indonesians contribute to the national Gross Domestic Product, contributing 60.5%. The number of Muslim populations in Indonesia is the most important compared to other countries, thus creating a large market for halal products. Objective: The research can provide an in-depth understanding of the market potential for Micro, Small, and Medium Enterprises focusing on halal products. This research also aims to understand how these halal products are related to the halal lifestyle, which is a lifestyle that complies with the principles of Islamic sharia in various aspects of life. Method: This research is considered most appropriate using a descriptive qualitative approach with a literature review. Data sources use secondary data. Furthermore, descriptive analysis techniques are used to analyze the collected data. Result: The results of the study show that to increase Indonesia's role in the global halal industry, steps are needed, such as halal certification, training and mentoring for Micro, Small, and Medium Enterprises, financial service facilities, and socialization regarding the importance of halal products. Implication: In general, the expected impact of this research is the creation of a more robust and more competitive ecosystem for halal Micro, Small, and Medium Enterprises in Indonesia, which will strengthen the national economy and improve Indonesia's position in the global halal industry.